La diversidad funcional intelectual como objeto de estudio histórico en España, 1900-1982 - Consuegra Regalado, Víctor (Historiografías, 2023)
The historical study of people with intellectual functional diversity in Spain constitutes a pending task of the academic historiography. However, it is possible to confirm that for the last two decades there has been a blooming of multidisciplinary publications that place the intellectual functional diversity in the core of their object of study. The purpose of this article is to address the investigations referred to people with intellectual functional diversity as active historical subjects in the history of Spain.KeywordsIntellectual functional diversity, disability history, history of medicine, Francoism, Transition